Nonswellable Injectable Hydrogels Self‐Assembled Through Non‐Covalent Interactions. Issue 10 (7th April 2017) - Becher, Tiago B.; Ornelas, Catia
Abstract: Injectable hydrogels have gained interest as drug delivery systems for the controlled release of drugs at specific locations. A simple strategy to obtain versatile supramolecular hydrogels has been developed, yielding transparent, self‐standing, nonswellable, biocompatible, biodegradable, shear‐thinning and self‐healing hydrogels. The gelification process occurs within seconds through ionic interactions between inorganic nanodiscs, an organic polymer and phosphate buffer solution. This strategy enables the inclusion of virtually any water‐soluble moiety, because there is no addition of organic solvents, metal catalysts, radical initiators or ultraviolet radiation. The new hydrogels present a shear storage modulus up to G'=1.3x10 4 Pa, one of the largest among those reported for non‐covalent hydrogels. The nonswelling and shear‐thinning behavior are crucial properties to the application of these new materials as injectable hydrogels. Abstract : Nonswellable hydrogels were developed using a very simple strategy based on non‐covalent interactions. These hydrogels are shear‐thinning, self‐healing, self‐standing, robust, biodegradable and biocompatible, making them valid candidates for injectable drug delivery systems.